Analisis Pengaruh Kepercayaan Konsumen Dan Life Style Terhadap Keputusan Pembelian Produk Glady 2 Glow - Hawa Afriani. A; Muhajirin Muhajirin; Ovriyadin Ovriyadin (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study examines the effect of consumer trust and lifestyle on purchasing decisions for Glady 2 Glow products. Using a quantitative approach with surveys and questionnaires, data were collected from 65 consumers and analyzed via multiple linear regression. The results show that both consumer trust and lifestyle significantly and positively influence purchasing decisions, highlighting their combined role in shaping consumer behavior. These findings provide practical insights for enhancing marketing strategies through improved product quality, service, and alignment with target consumers’ lifestyles, while also contributing to marketing theory and future research.